Systematic functional analysis and potential application of a serine protease from cold-adapted Planococcus bacterium - Weijun Leng; Xiaoyun Wu; Xianghui Qi; Hongying Liu; Li Yuan; Ruichang Gao (Food Science and Human Wellness)
In this study, a gene encoding serine protease (PmSpr288) from cold-adapted bacterium, namely Planococcus maritimus XJ11, was cloned and overexpressed in Escherichia coli BL21 (DE3). Bioinformatics analysis revealed that PmSpr288 belongs to serine protease S8 superfamily with a classical catalytic triad comprised by the Asp49, His86 and Ser251. Moreover, PmSpr288 was found to be active over broad alkaline pH and low-moderate temperature, and exhibited wide range of protein substrate specificity. In addition, PmSpr288 was able to hydrolyze the meat proteins actin and myosin, and molecular docking results suggested that the crucial interaction between PmSpr288 and actin/myosin complexes was mainly occupied by hydrogen bonds. The muscle protein hydrolysates of silver carp prepared by PmSpr288 was shown to have antioxidant activity via DPPH radical scavenging assay, which presented an IC50 valve of 1.309 mg/mL. In conclusion, these characteristics imply that PmSpr288 has potential biotechnological application prospect for the production of bioactive peptides.